FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Asri Cahyati, 11.05.52.0065; Susilowati, Yeye (Students Journal of Accounting and Banking, 2015)
The purpose of this study was to analyze the influence of the commissioners, leverage, company size, profitability and managerial ownership on the disclousure of corporate social responsibility. The populations of this study is manufacturing companies which are listed in Indonesia Stock ExchangedÂ during 2010 â 2013. The samples were selection using purposive sampling method is manufacturing company amount 27 companies. Technique test of data is by using multiple linear regression analysis. The analysis showed that the variables have a significant positiveeffect on the diclosure of corporate social responsibility is leverage. While commissioners,company size, profitability and managerial ownership does not significanly influence the disclosure of corporate responsibility.Keywords: Commissioners, Leverage, Company Size, Profitability and Managerial Ownership